BANANA AND PLANTAIN AS MEDICINAL FOOD - Nurhayati Nurhayati; Dedy Eko Rahmanto (UPT Penerbitan Universitas Jember)
Indonesia is mega diversity country with25.000-30.000 plant species has 6.000 species ofmedicinal plants [1]. One of potential plants to beexplored as medicinal plants is banana. The plantfamily Musaceae, composed of bananas, plantains,and ornamental bananas, originally evolved inSoutheast Asia and surrounding tropical andsubtropical regions. More than 145 million tons ofbanana and plantain were produced worldwide in2011 according to FAO estimates. Banana are grownin nearly 130 countries. In addition to fruit, bananasand plantains provide many cultures with medicines,beverages, fibers, edible floral parts, dyes, fuel,steam for cooking, cordage, wrapping materials, etc[2].Bananas are among the world’s leading foodcrops, after rice, wheat and maize. Banana is dessertfruit that its edible part is pulpy, firm to tender, freefrom seeds or pips, and has a characteristic flavour.Plantain is a cooking banana subgroup. Plantainresemble banana but are longer in length, have athicker skin, and contain more starch. Most dessertbanana cultivars in the world are AA or AAA, this lastgroup includes almost all the cultivars sold to exportmarket. Cooking bananas, often named plantains,are mostly AAB, ABB, or BBB [3,4].Banana and plantain are important staplefoods in many developing countries, especially inIndonesia. Musa are rich in vitamin C, B6, minerals,and dietary fiber. They are also a rich energy source,with carbohydrates accounting for 22% and 32% offruit weight for banana and plantain, respectively.People annually consume 28 kg of banana andplantain per capita, or 155 kg per year, or almost halfof 1 kg per day. Four African countries have thehighest per capita consumption of banana/plantainin the world, with Uganda having the highest [2].Recent knowledge diet may modulate variousfunctions in the body and may play detrimental orbeneficial roles in some diseases. Foods areexpanding from emphasis on survival, hungersatisfaction, and preventing adverse effects toemphasizing the use of foods to promote a state ofwell-being and better health and to help reduce therisk of disease. The study investigated thebeneficial/healthy